(untitled) (International Journal of Physiology, 2020)
The study was conducted to evaluate the effect of pranayam (yogic controlled breathing exercises) & meditation on cardiovascular parameters in 1st year male medical students of GSVM Medical College, Kanpur. All the 60 students selected for the study were randomized into 3 groups of 20 students each: Group I–Anulom Vilom Pranayam, Group II–Kapalbhati Pranayam, Group III–Bhastrika Pranayam. Blood pressure (systolic & diastolic) & pulse rate of all the students in each group were recorded at baseline & after 3 months of training. Training programme included 10 min. meditation in padmasana followed by 5 min. practice of pranayam twice a day for 3 months. A significant (p< .001) decrease in pulse rate, systolic BP and diastolic BP were observed after 3 months of training.. The relaxation & flexibility induced by meditation & pranayam help to stabilize the autonomic nervous system with a tendency towards parasympathetic dominance. So the meditation & pranayam should be encouraged to improve the performance of cardiovascular system. Controlled pranayam breathing is also effective in improving the strength & tone of muscles involved in respiration.